Death Registration System in I.R.Iran - N Jafari; MJ Kabir; ME Motlagh (Tehran University of Medical Sciences, 2009)
Death and disease information are key information in priority setting. Because importance of valid and reliable mortality data, death registration system in I.R.Iran as a multi source registration system was established and improved from 1998. In this system mortality data are collected from hospitals, health houses and health centers, forensic medicine bureau, authorized cemeteries, civil registration bureau and other probable sources in district and within a defined process data are collected in provincial health centers and then in ministry of health. For improvement of registered data some important activities have to done in different level such as continuous education and strengthening intersectoral collaboration.